2004
DOI: 10.1021/je030131q
|View full text |Cite
|
Sign up to set email alerts
|

Bubble Temperatures of the Binary Mixtures of Dimethylcarbonate with Some Alcohols at 95.8 kPa

Abstract: Boiling temperatures at 95.8 kPa over the entire composition range are measured for the binary systems formed by dimethylcarbonate with ethanol, n-propanol, isopropanol, n-butanol, isobutanol, sec-butanol, and tert-butanol. A Swietoslawski-type ebulliometer was used for the measurements. The composition vs temperature measurements are well represented by the Wilson model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…For the case of the isothermal condition, Oh et al 19 only reported the vapor and liquid mole fractions (y−x) without the values of the corresponding equilibrium pressures. For the case of isobaric conditions, Vittal et al 21 and Matsuda et al 22 only report the equilibrium temperature and the liquid mole fraction (T−x) at selected isobaric conditions from 40 to 95.8 kPa, whereas Rodriguez et al 20 report a complete and consistent (T−x−y) data at 101.3 kPa. According to Oh et al, 19 Vittal et al, 21 Matsuda et al, 22 and Lecat, 23 this mixture is zeotropy at the explored range, while Rodriguez et al 20 declare that VLE of this binary mixture displays an azeotropic behavior at 101.3 kPa (i.e., T Az = 363.32 K and x 1 Az = 0.9306).…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the case of the isothermal condition, Oh et al 19 only reported the vapor and liquid mole fractions (y−x) without the values of the corresponding equilibrium pressures. For the case of isobaric conditions, Vittal et al 21 and Matsuda et al 22 only report the equilibrium temperature and the liquid mole fraction (T−x) at selected isobaric conditions from 40 to 95.8 kPa, whereas Rodriguez et al 20 report a complete and consistent (T−x−y) data at 101.3 kPa. According to Oh et al, 19 Vittal et al, 21 Matsuda et al, 22 and Lecat, 23 this mixture is zeotropy at the explored range, while Rodriguez et al 20 declare that VLE of this binary mixture displays an azeotropic behavior at 101.3 kPa (i.e., T Az = 363.32 K and x 1 Az = 0.9306).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Previous thermophysical evaluation of this binary mixture covers the vapor–liquid equilibrium (VLE) measurement under the isothermal condition of 333.15 K and at the isobaric conditions from 40 to 101.3 kPa. However, the available experimental VLE data are partially reported. For the case of the isothermal condition, Oh et al only reported the vapor and liquid mole fractions ( y – x ) without the values of the corresponding equilibrium pressures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation